THE OLIVE MONOCULTURE IN THE SOUTH OF SPAIN - SÁNCHEZ-MARTÍNEZ, José D; PANIZA CABRERA, Antonia (European Journal of Geography, 2023)
Olive trees have been cultivated for thousands of years in their preferred climate, the Mediterranean, with Spain being the world’s biggest producer of table olives and olive oil. The globalization of recent decades has intensified specialization in this crop in the south of the country where a significant geographic expansion of the olive groves has been accompanied by substantial growth in the total harvest, due to an increase in the intensity and productivity of olive farming. These swift changes have had serious social and environmental consequences many of which have been caused by poor management of basic natural resources. At the same time the introduction of new plantation systems and the variety of physiographical resources and economic structures on which the olive groves are based has enabled us to identify significant agricultural and landscape diversity. In this article we will be looking at the province of Jaén as an illustrative example of these changes.